Visualization Method of Heat Risk through Light Environment Reproduction Considering Cloud Coverage - Shibata Ryoya; Ozaki Taira; Kubota Satoshi; Yasumuro Yoshihiro (E3S Web of Conferences)
In recent years, the number of heatstroke patients in Japan has been increasing, necessitating public awareness and precautions. While the Ministry of the Environment provides heat index information for urban area scales online, there are no means to obtain localized heat index data. Previous studies have visualized the heat index of varying heat environments using game engines based on public 3D data and meteorological information by rendering sunlight and shadows as computer graphics (CG). However, the applicability is limited to clear weather conditions. This study focuses on the fact that heat stress on the human body depends not only on solar radiation but also on meteorological factors such as humidity and that the risk of heatstroke is not necessarily higher only under clear weather. We develop a model to estimate cloud cover parameters from observed meteorological elements. By generating cloud cover within the game engine according to the weather conditions, we reproduce the celestial light environment and expand the applicability of heat risk visualization.